A Mine Ventilation System Energy Saving Technique Based on an Improved Equilibrium Optimizer - Yu, Bao-cai; Shao, Liang-shan (Frontiers in Energy Research, 2022)
Over the years, the ventilation systems used in coal mines have become more and more complex. Due to a lack of scientific and effective management, the energy consumed by ventilation systems has rapidly increased, resulting in considerable wasted energy. To solve this problem, the authors established a nonlinear optimization model aimed at minimizing the total energy consumption of a mine ventilation network. Furthermore, the authors propose an improved equilibrium optimizer algorithm to solve the model. First, the population is initialized by a chaotic map. Second, the adjustment strategy of a trigonometric function is introduced to improve the index F, which improves the global development ability of the algorithm, avoids falling into local optimum, and can improve the local search ability in the later stages. Then, Gaussian disturbance is introduced to enhance the diversity of particles and avoid falling into the local optimum. Finally, a learning factor was introduced to improve the generation rate G and improve the algorithm’s integrity; it was then compared with other algorithms. The simulation results show that the performance of the improved algorithm is significantly better than other algorithms. It was tested with the ventilation system of Wangjialing mine of Zhongmei Huajin Energy Co., Ltd. The results showed that the energy consumption of the ventilation system was reduced by 17.83%. This method can save the mine about 2 million yuan RMB every year. The economic effect is remarkable, we achieved the purpose of energy conservation and emission reduction, and the effectiveness of the proposed method was verified.